2021
DOI: 10.1111/1475-6773.13739
|View full text |Cite
|
Sign up to set email alerts
|

Differences in health care spending and utilization among older frail adults in high‐income countries: ICCONIC hip fracture persona

Abstract: Objective: This study explores differences in spending and utilization of health care services for an older person with frailty before and after a hip fracture. Data Sources: We used individual-level patient data from five care settings. Study Design: We compared utilization and spending of an older person aged older than 65 years for 365 days before and after a hip fracture across 11 countries and five domains of care as follows: acute hospital care, primary care, outpatient specialty care, post-acute rehabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 31 publications
2
52
0
Order By: Relevance
“…Second, after England, we found that the United States ranks the second highest for 365-year mortality across both personas. This is notable, as the United States spends comparatively more resources caring for these patients 16,17 and suggests that they are the least efficient system. Unlike England, the United States has slightly lower average 30-day mortality for both personas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, after England, we found that the United States ranks the second highest for 365-year mortality across both personas. This is notable, as the United States spends comparatively more resources caring for these patients 16,17 and suggests that they are the least efficient system. Unlike England, the United States has slightly lower average 30-day mortality for both personas.…”
Section: Discussionmentioning
confidence: 99%
“…This is likely influenced by several factors, including differences in the amount of time patients spend in the hospital and differential use of postacute care rehabilitative services or long-term care. 16,17 Unfortunately, the majority of countries lack comprehensive data on long-term care and postacute rehabilitative care, limiting our ability to explore these relationships further. Of note, in-hospital mortality was weakly inversely associated with readmission rate, suggesting a problem of competing risk.…”
Section: Discussionmentioning
confidence: 99%
“…States prior to death and likely more time during end-of-life care spent in postacute rehabilitative facilities. 54 We also encountered important differences across some coun- In part, the variation in use and costs across countries in each health care sector (e.g., hospitals) may be driven by differences in the roles and functions of that sector. For example, rehabilitation in some countries may be a part of a hospital's routine functions-whereas in other countries, much of this care may be provided in specialized clinics or in the community.…”
Section: Discussionmentioning
confidence: 99%
“…In other analyses from the ICCONIC collaborative on the acute stage of care for hip fracture patients, Germany was shown to have the longest inpatient acute stays, which may also be associated with the increased likelihood to discharge home. 10 When patients in Germany were admitted to institutional LTC, they were most likely to be discharged to home. While in France, institutional LTC becomes the permanent residence for older patients who rarely return home after being admitted to institutional LTC.…”
Section: Discussionmentioning
confidence: 99%